Masquerade syndrome: an ocular involvement of lung cancer. - Umi Kalthum MN; Wan Haslina Wah (Penerbit UKM, 2013)
We report a case of a 37-year-old smoker who presented with painless and sudden onset of loss of upper field vision of the right eye, associated with one month history of dry cough which was unresponsive to antibiotic and subsequent anti- tuberculosis therapy. Visual acuity at presentation was counting finger. There was bullous retinal detachment on examination. Radiological imaging revealed multiple lung opacities, involving the brain and the right orbit. Bronchoscopy and biopsy confirmed the diagnosis of adenocarcinoma of the lung. This case illustrates masquerade syndrome of which a lung carcinoma harbours behind a seemingly innocent retinal detachment. It also highlights the importance of entertaining lung carcinoma as a differential diagnosis in suspected tuberculosis among heavy smokers.